Profil GC-MS Ekstrak Mitragyna speciosa Korth. asal Kalimantan Selatan - Hayatun Izma; Normaidah (JURNAL FARMASI DAN MAKANAN, 2026)
Mitragyna speciosa Korth. (kratom) has attracted attention due to its alkaloid content, biological activity, and potential for misuse. This study aimed to characterize the secondary metabolite profile of M. speciosa extract using Gas Chromatography–Mass Spectrometry (GC-MS) to identify major marker compounds and establish a chemical fingerprint for sample verification. The sample used was an ethanolic extract of kratom leaves collected from Hulu Sungai Selatan, South Kalimantan, and analyzed using GC-MS. The results showed three major compounds, with mitragynine (25.14%), Corynan-16-carboxylic acid, 16,17-didehydro-9,17-dimethoxy-, methyl ester (3β,16-E) (25.38%), and rhynchophylline (18.89%) as the dominant constituents. These compounds are associated with various biological activities, particularly in the nervous and cardiovascular systems. The findings provide an overview of the chemical compounds in South Kalimantan kratom by GC-MS and may serve as a scientific basis for sample identification, evidence-based kratom monitoring, and further studies related to its potential applications and safety.